Epigenetic regulation of miR-212 expression in lung cancer. - Mariarosaria Incoronato; Loredana Urso; Ana Portela; Mikko O Laukkanen; Ylermi Soini; Cristina Quintavalle; Simona Keller; Manel Esteller; Gerolama Condorelli (PLoS ONE, 2011)
Many studies have shown that microRNA expression in cancer may be regulated by epigenetic events. Recently, we found that in lung cancer miR-212 was strongly down-regulated. However, mechanisms involved in the regulation of miR-212 expression are unknown. Therefore, we addressed this point by investigating the molecular mechanisms of miR-212 silencing in lung cancer. We identified histone modifications rather than DNA hypermethylation as epigenetic events that regulate miR-212 levels in NSCLC. Moreover, we found that miR-212 silencing in vivo is closely associated with the severity of the disease.